(untitled) (Indian Journal of Animal Production and Management, 2014)
The study was conducted to record the basic information on sexual behaviour and semen quality of four Swamp buffalo bulls maintained at “Network Project on Swamp Buffalo,” Department of Animal Genetics and Breeding, College of Veterinary Science, Khanapara, Guwahati, Assam. A total of 160 ejaculates, 40 ejaculates from each bull collected by Artificial Vagina (AV) method were utilized for the present study. During approach towards the teasers, 26.95% bulls were found aggressive, 51.72% were active and 21.38% were dull. After approaching the teaser, tactile stimulations, like sniffing (38.19%), smelling (17.36%), licking (36.11%), bunting (49.30%), flehmen posture (43.50%) and chin resting (37.50%) were observed. Reaction time ranged from 6 to 20 seconds and ejaculate time from 10 to 40 seconds. The dismounting time was from 10 to 15 seconds. Out of 160 ejaculates, the colour of semen was creamy white, milky white and light yellowish in 50.00, 31.25 and 18.75 per cent ejaculates respectively. The difference between bulls was significant (P< 0.01) for ejaculate volume, mass activity, initial sperm motility, sperm concentration, total HOST reacted spermatozoa and total head abnormalities (P< 0.05) while live sperm, live intact acrosome, mid piece abnormalities and tail abnormalities did not differ significantly between bulls.